ERICA: sexual initiation and contraception in Brazilian adolescents - Borges, Ana Luiza Vilela (Rev Saude Publica, 2016)
OBJECTIVE: To estimate the prevalence of sexual initiation and contraceptive use at the last sexual intercourse of Brazilian adolescents, according to sociodemographic features. METHODS: The data were obtained from the Study of Cardiovascular Risks in Adolescents (ERICA), a national school-based cross-sectional study. We included 74,589 adolescents from 32 geographic strata (27 capitals and five sets of municipalities with more than 100,000 inhabitants of each of the five macro-regions of the Country). Information on sexual initiation and contraceptive use at the last sexual intercourse (male condom and oral contraceptive pill) has been used. We have estimated prevalence and confidence intervals (95%CI) considering sample weights according to sex, age, type of school, residence status, macro-region and capitals. RESULTS: We observed that 28.1% (95%CI 27.0-29.2) of the adolescents had already initiated sexual life, with higher prevalence among those aged 17 years (56.4%, 95%CI 53.9-58.9), males (33.5%, 95%CI 31.8-35.2), studying at public schools (29.9%, 95%CI 28.5-31.4), and from the Northern region (33.9%, 95%CI 32.3-35.4), mainly from Macapa, Manaus, and Rio Branco. Among those who had started their sexual life, 82.3% (95%CI 81.1-83.4) reported the use of contraceptive methods at the last intercourse, and the prevalence of use was higher among adolescents aged 17 years (85.3%, 95%CI 82.7-87.6), females (85.2%, 95%CI 83.8-86.5) and those living in the Southern region (85.9%, 95%CI 82.9-88.5). Male condom was used by 68.8% (95%CI 66.9-70.7), with no difference by type of school or macro-regions; the contraceptive pill was used by 13.4% (CI95% 12.2-14.6), and more frequently used among women (24.7%, 95%CI 22.5-27,0) and 17-year-old adolescents (20.8%, 95%CI 18.2-23.6) from urban settings(13.7%, 95%CI 12.5-14.9) and from the Southern region (22.6%, 95%CI 19.0-26.8), and less often in the Northern region. CONCLUSIONS: ERICA’s data analysis on sexuality and contraception shows heterogeneities in the prevalence of sexual initiation and use of contraceptive methods among Brazilian adolescents, depending on their age, where they live, and the type of school they study at. Younger adolescents and those living in the Northern region seem to be more vulnerable to the consequences of unprotected sexual intercourses.